مساهمة المؤشرات المالية الحديثة بالتنبؤ بالفشل المالي في المؤسسة الاقتصادية - نريمان, قادري; خلود, بركة; ناريمان, موساوي (جامعة الوادي - University of Eloued, 2023)
"هدفت هذه الدراسة إلى التعرف على مساهمة المؤشرات المالية للتنبؤ بالفشل المالي للمؤسسة الاقتصادية من اجل التعرف على وضعية تلك المؤسسة واتخاذ الإجراءات المناسبة , وهذا ما أدى إلى ظهور العديد من النماذج التي تبنى على مؤشرات محددة تعطي لها أوزان معينة تختلف من نموذج لأخر و ذلك من اجل التنبؤ باحتمالات الفشل في وقت مبكر , ومن اجل ذلك تم الاعتماد على المنهج التحليلي و كذالك دراسة حالة وقد توصلت الدراسة إلى عدت نتائج أهمها : بينت نتائج تحليل المؤشرات المالية الرئيسية أن هناك ضعفا في أداء المؤسسة من خلال المؤشرات السلبية الكثيرة التي ظهرت لدينا في مؤشر خلق القيمة و مؤشر الاقتصادي من خلال الربح الاقتصادي . مما يؤكد اقترابها كثيرا من الفشل . وكذلك من خلال استخدام نموذج Altman و Kida تم التوصل بأن المؤسسة معرضة لخطر الفشل المالي خلال سنوات الدراسة 2019 , 2020 و 2021 , فحسب Altman في جيله الأول و الثاني و الثالث فان المؤسسة تقع في المنطقة الحمراء أي أن المؤسسة معرضة للفشل لان النتيجة اقل تماما من 1.81(Z≤1.81) في الجيل الأول و في الجيل الثاني تحتاج إلى دراسة أكثر تفصيلا للتنبؤ بوضعيتيها(Z≥1.23) و في الجيل الثالث (Z≤1.1)تؤكد بان المؤسسة معرضة للفشل , أما نموذج Kida يتوقع أن المؤسسة مهددة بخطر الإفلاس كون قيمة Z سالبة -0.5 دليل على أن المؤسسة معرضة لخطر الفشل المالي . أما بخصوص المؤسسة فقد اقترحنا جملة من الاقتراحات مفادها أن على المؤسسة تطبيق سياسات محاسبية واضحة و محددة بشأن الإفصاح المبكر عن البيانات و المؤشرات المالية لإتاحة الفرصة لتطبيق النموذج و الوقوف على نتائجه أول بأول . " "This study aimed to identify the uses of financial indicators to predict the financial failure of an economic institution in order to identify the status of that institution and take appropriate measures, and this led to the emergence of many models that are built on specific indicators that give them certain weights that differ from one model to another, in order to predict The possibility of failure at an early date, and for that, the approach was relied on the descriptive analytical method, as well as a case study. The study reached several results, the most important of which are: Through the use of the Altman model, as well as the kida model, it was concluded that the Sonelgaz institution is at risk of financial failure during the years of study, according to the Altman model, the institution is located in the red zone, meaning that the institution will go bankrupt because the model result is less than 1.8 (Z<1.8). kida It is expected that the institution is at risk of bankruptcy, since the value of Z is negative 0.5 - evidence that the institution is at risk of financial failure, as well as the results of the analysis of the main financial ratios that make up the models,that there is a weakness in the performance of the institution, the sample of the research, through the many negative indicators that appeared to us, Which confirms its failure or very close to failure. With regard to the institution, we have proposed a set of recommendations that the institution should implement clear and specific accounting policies regarding early disclosure of financial data and indicators, to provide an opportunity to implement the model and see its results in a timely manner. "
Keywords: المؤشرات المالية , الفشل المالي للمؤسسات , نماذج التنبؤ بالفشل المالي , نموذج Altma, نموذج Kida; Financial indicators, Corporate financial failure, Financial failure prediction models Altman model, kida model.